Analisis Rasio Solvabilitas terhadap Kinerja Keuangan PT Garuda Indonesia di Masa Pandemi - Sarah Azzahra (Program Studi Manajemen Universitas Muslim Maros, 2021)
The research we are currently conducting aims to assess and compare the company's financial capacity to the performance of PT Garuda Indonesia before and during the pandemic. The type of research we use is quantitative research, in which to analyze the effect of the solvency ratio on the financial statements of PT Garuda Indonesia for the last 4 years, namely the 2017-2020 period. In this study, we conclude that the Covid-19 pandemic has an influence on company finances. The company's performance is considered to have decreased when compared to the previous period. Due to the Covid-19 pandemic, which required the closure of the operations of various business sectors, including the aviation sector, this resulted in a decline in company revenues. The Covid-19 pandemic also caused fluctuations in the value of the Debts to Asset Ratio (DAR) and Debt to Equity Ratio (DER). The percentage of the company's DAR and DER values ​​exceeds industry standards. The DAR value of the company has increased drastically. Meanwhile, the DER value has decreased drastically to a minus. Of the various impacts arising from the Covid-19 pandemic, PT Garuda Indonesia is predicted to experience financial distress, which means that the company's condition is in the worst condition, therefore the company is expected to take actions as a step to overcome the problems it is facing.